2015
DOI: 10.1007/s10100-015-0393-8
|View full text |Cite
|
Sign up to set email alerts
|

Portfolio performance measurement using differential evolution

Abstract: The basic problem in finance theory is the selection of an appropriate mix of assets in a portfolio in order to maximize portfolio expected return and subsequently to minimize portfolio risk. Another approach takes into account portfolio performance expressed by various measurement techniques e.g. Sharpe ratio, Treynor ratio, Jensen's alpha, Information ratio, Sortino ratio, Omega function and Sharpe Omega ratio that are focused on determine the allocation of the available resources in the selected group of as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 16 publications
0
10
0
Order By: Relevance
“…This means that an investment with a higher Sortino Ratio per additional unit of negative risk taken will generate more return than an investment with a lower Sortino Ratio. It can therefore be concluded that the Sharpe ratio penalises the investor for positive volatility, above the MAR, whereas the Sortino ratio does not (Pekar, Čičková, & Brezina, 2015).…”
Section: Sortino Ratiomentioning
confidence: 95%
“…This means that an investment with a higher Sortino Ratio per additional unit of negative risk taken will generate more return than an investment with a lower Sortino Ratio. It can therefore be concluded that the Sharpe ratio penalises the investor for positive volatility, above the MAR, whereas the Sortino ratio does not (Pekar, Čičková, & Brezina, 2015).…”
Section: Sortino Ratiomentioning
confidence: 95%
“…The algorithms’ steps are described in detail, e.g. [ 68 , 69 ], and the principle of the basic version of differential evolution can be characterized by the pseudocode listed in [ 63 , 65 ].…”
Section: Differential Evolution For the Location Of Osmimentioning
confidence: 99%
“…In the solution procedure, it was necessary to set the values of the differential evolution algorithm’s parameters, and the values were set based on experiments conducted in previous research, according to [ 63 , 74 ]:…”
Section: Location Of Nesting Aids In An Orchard With Randomly Placmentioning
confidence: 99%
See 1 more Smart Citation
“…The algorithms' steps are described in detail, e.g. [68,69], and the principle of the basic version of differential evolution can be characterized by the pseudocode listed in [63,65].…”
Section: Differential Evolution For the Location Of Osmia Nesting Aidsmentioning
confidence: 99%